The Relationship Between the Brain and First Language Acquisition in Children - Anwar Sidik; Ahmad Husein; Nur Hidayah (Arabiyyatī: Journal of Arabic Language Education, 2025)
First language acquisition in children is a complex and multidimensional process, as it involves the interaction of biological, neurological, cognitive, and social environmental factors. The brain, as the center of the nervous system, plays a crucial role in processing, storing, and producing language from early stages of life. This study aims to explain the role of the brain in children’s first language acquisition dan to explain the influence of the environment on brain activation and language development. This study employs a literature review methodology to explore the relationship between gadget use intensity, biological mechanisms, and early childhood language development. Using thematic and descriptive qualitative analysis, the study synthesizes existing research to understand how neurological, environmental, and technological factors interact in shaping children’s language acquisition. Children’s first language acquisition is strongly influenced by brain maturation and environmental stimulation. Neurological development, particularly the maturation of language-related areas such as Broca’s area and Wernicke’s area, provides the biological foundation for language comprehension and production. Brain plasticity in early childhood allows neural networks to develop efficiently through meaningful linguistic experiences. However, biological readiness alone is insufficient without environmental support. Rich and interactive environments—especially within the family and educational settings—play a crucial role in activating language-related brain functions. Frequent verbal interaction, responsive communication, and social engagement strengthen neural connections, supporting optimal receptive and expressive language development. Future studies should use empirical and longitudinal methods to examine gadget use, parental mediation, and neurological factors influencing early childhood language development across diverse contexts.